2017
DOI: 10.21767/2471-299x.1000063
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adverse Pregnancy Outcomes among mothers who gave birth from Jan 1-Dec 31/2015 in Jimma University Specialized Hospital, Case control study, 2016

Abstract: Background: Adverse pregnancy outcomes lead to serious health consequences to the mother and/or the baby. These Adverse birth outcomes; prematurity, low birth weight and still birth represent significant problems in both developing and developed countries. Adverse pregnancy outcomes are still major public health problems in developing countries including Ethiopia where most pregnancies are unplanned, complications are many and outcomes are generally Unfavorable for both mother and infant.Objective: To identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 2 publications
9
28
0
Order By: Relevance
“…24,25 This finding is also supported by studies from the Jimma University Specialized Hospital and the Dessie Referral Hospital, which showed that obstetric complications during current pregnancy and complications during labor and delivery were strongly associated with adverse birth outcomes (low birth weight, preterm birth, low APGAR score, and still birth). [26][27][28] Referral linkage was found to be significantly associated with NNM in this study, increasing the odds of NNM by three-times compared to mothers who were not referred. This result is in line with a study by the Jimma University Specialized Hospital, which revealed that referral of mothers with complications from other facilities for delivery service was high risk for adverse pregnancy outcomes when compared to mothers who were not referred.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…24,25 This finding is also supported by studies from the Jimma University Specialized Hospital and the Dessie Referral Hospital, which showed that obstetric complications during current pregnancy and complications during labor and delivery were strongly associated with adverse birth outcomes (low birth weight, preterm birth, low APGAR score, and still birth). [26][27][28] Referral linkage was found to be significantly associated with NNM in this study, increasing the odds of NNM by three-times compared to mothers who were not referred. This result is in line with a study by the Jimma University Specialized Hospital, which revealed that referral of mothers with complications from other facilities for delivery service was high risk for adverse pregnancy outcomes when compared to mothers who were not referred.…”
Section: Discussionsupporting
confidence: 47%
“…This result is in line with a study by the Jimma University Specialized Hospital, which revealed that referral of mothers with complications from other facilities for delivery service was high risk for adverse pregnancy outcomes when compared to mothers who were not referred. 26 This finding might be due to the fact that referral cases were from mothers who faced obstetric complications and needed more timely and better interventions to avoid maternal and neonatal morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Referral linkage was significantly associated with neonatal near miss. This result is in line with study in Jimma university specialised hospital , revealed that referral of mothers with complications from other facility for delivery service was high risk for adverse pregnancy outcomes than mothers who were not referred [22].This is might be due to the fact that referral cases were from mothers who faced obstetric complications and needs timely and better intervention to avoid maternal and neonatal morbidity and mortality.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is supported, studies in Jimma university specialised hospital and Dessie referral hospital, shows that obstetric complication during current pregnancy and complication during labor and delivery were strongly associated with adverse birth outcomes(low birth weight ,preterm birth, low APGAR score and still birth) [22][23][24].…”
Section: Discussionsupporting
confidence: 73%
“…Older maternal age was associated with a higher risk of adverse pregnancy outcome [ 15 ]. Women who had primary education or above were less likely to have had adverse pregnancy outcomes compared to those with no education [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%